Frontispiece: Racemisation in Chemistry and Biology. Issue 17 (27th March 2020) - Ballard, Andrew; Narduolo, Stefania; Ahmed, Hiwa O.; Keymer, Nathaniel I.; Asaad, Nabil; Cosgrove, David A.; Buurma, Niklaas J.; Leach, Andrew G.
Abstract : When chemistry meets biology, as in the image with a child stumbling upon the enantiomers of cetirizine in the sea, stereochemistry often governs the outcome. In aqueous environments, the process of racemisation will therefore be important and can be facilitated in a range of ways including by base, acid or enzymatic catalysis. The limited information concerning racemisation under each of these conditions is surveyed and critiqued. Tools to guide prediction of racemisation risk are presented. For more details, see Review article by A. Ballard et al. on page 3661 ff.